Príspĕvek k otázce vlivu profesionální expozice styrenu na metabolismus lipidů a lipoproteinů - Buresová, E; Zadák, Z; Hassman, P; Sobotka, L (Sbornik vedeckych praci Lekarske fakulty Karlovy univerzity v Hradci Kralove. Supplementum, 1991)
A total of 53 subjects with working exposure to styrene (1-29 years) has been investigated. On lipid and lipoproteins examination, only 8 persons (15%) showed normal values. The amount of 26 (49%) persons had the increase in HDL-cholesterol values. Subjects with protracted exposure to styrene (11-29 years) had higher level of cholesterol, absolute HDL-cholesterol values, total VLDLs and atherogenic index as compared to those which have worked at risk of styrene for 1-10 years. However, there was no statistically significant difference. Occupationnaly styrene exposed persons had statistically higher HDL-cholesterol (expressed both absolutely and relatively) in comparison with 21 clinically healthy controls. Changes of total cholesterol, VLDLs and of atherogenic index may partly be explained with factor of age. However, this is no such an explanation for HDL-cholesterol, since in adverse to that it decreases with more age in a normal population. Authors assume the pathologically higher HDL-cholesterol levels may exhibit causal interaction with occupational exposure to styrene, probably through the induction of microsomal liver enzymatic systems.
Keywords: dospělí; Female; Styrene; Adult; ženské pohlaví; lipoproteiny; Adolescent; lipidy; lidé; Occupational Exposure; styreny; Lipids; Styrenes; Male; pracovní expozice; Aged; styren; lidé středního věku; senioři; mužské pohlaví; Lipoproteins; Middle Aged; mladiství; Humans